PHYTOCHEMICALS AND ANTIMICROBIAL ACTIVITY OF TERMINALIA SCHIMPERIANA HOSTCH (COMBRAETACEA) PLANT USED IN TRADITIONAL MEDCINE - Mohammed, A. H; Balogun, O . L; Mshelia, E. H; Sambo, S. M; Ogunleye, J. A (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
This study investigated the phytochemicals and antimicrobial activity of leaves and bark of Terminalia scheamperiana Hostch,(combraetaecea) plant. Terminalia scheamperiana hostch plant is extensively used as traditional medicine in most part of Africa. It is a source of many potent biological compounds. The leaves and bark of T. Scheampriana were serially extracted with hexane, ethyl acetate, acetone, ethanol and water by soxhlet extraction method. The preliminary phytochemical analysis carried out on the different extract showed high concentration of Saponin and Tannin in the bark extract of ethanol with appreciable amount of glycoside and anthraquinone were also observed. Anthraquinone was not detected in all the leaves extract of T. Scheamperiana analysed. Anti microbial susceptibility test using disc diffusion method shows highest zone of inhibition in bark extract of ethanol with inhibition diameter of 12mm for S. typhi,14mm for S. aureus,12mm for kleb, and 11mm for E. coli at a concentration of 100 g/disc. Aqueous extract of leaves gives inhibition diameter of 14mm for S. typhi, 18mm for S. aureus at 100µg/disc concentration. 22mm inhibition zone was also observed in leaves extract of acetone against S. aureus at 100µg/disc concentration. Ciproflaxacine, 10µg/disc concentration was used as reference standard and have inhibition diameter ranging from 35 to 45 for the various specie of the bacteria tested. Little activity was observed in candida with an inhibition diameter of 11 and 8mm in leaves and bark extract of ethyl acetate respectively. Ketoconazole, 10µg/disc concentration was used as reference standard and have inhibition diameter ranging between 17 and 18mm. Minimum inhibitory concentration (MIC), was determined using serial micro dilution assay. The micro organism tested are; Staphylococous aureus (gram positive bacteria) and Salmonela typhi (gram negative) bacteria. All the extracts were active against the selected pathogens at a concentration of 125µg/ml, except for the extract of ethanol and acetone where growth was observed at that concentration. However all the test organism exhibit growth when all the contents in the MIC test tubes were sub cultured into nutrient agar for MBC analysis. This justified the fact that the leaves and bark of T. Schempheriana is bacteriostatic and not bacteriocidal. MIC for candida was not determined as little activity is observed in susceptibility testing. The plant can therefore be recommended for used as traditional medicine. Further research is recommended to be carried out on anti malarial activity on the plant material. Research is also recommended to be carried out on the plant to isolate the most active compounds for the development of drugs. The activity found in Terminalia schemperiana plant could be a lead in the development of antimicrobial agents.